2015
DOI: 10.1080/17461391.2015.1017538
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the impacts of continuous and interval cycle exercise on perceived exertion

Abstract: Ratings of perceived exertion (RPE) were developed to assess exertion during exercise testing. However, assessments of RPE prior to and after exercise have become common and potentially important in understanding exercise behaviour. The purpose of this project was to compare RPE taken before, during and after interval and continuous exercise sessions. Twenty-four participants (12 men, 12 women, body mass index = 24, VO2peak = 41 mL · kg · min(-1)) completed a maximal cycle ergometer test used to prescribe expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Enjoyment and affective valence decreased significantly, and HR increased significantly during exercise in all sessions with a significant effect of menstrual cycle phase. These results partially corroborate earlier research that observed a comparable association between an increase in exertion and HR, coupled with a reduction in affective responses within the context of both HIIT (12,16) and continuous exercise (13,28).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Enjoyment and affective valence decreased significantly, and HR increased significantly during exercise in all sessions with a significant effect of menstrual cycle phase. These results partially corroborate earlier research that observed a comparable association between an increase in exertion and HR, coupled with a reduction in affective responses within the context of both HIIT (12,16) and continuous exercise (13,28).…”
Section: Discussionsupporting
confidence: 91%
“…HIIT can be defined and utilized in numerous ways but is characterized by repeated, brief exposures to nearmaximal exercise followed by passive or active recovery periods at very low intensities (10). Studies have demonstrated that this approach promotes significant changes in fitness (9,10) and can positively impact affective responses and reduce perceived exertion (11,12). Although numerous studies have considered the physiological and psychological implications of HIIT, one other potentially important factor worthy of consideration is the menstrual cycle.…”
mentioning
confidence: 99%